2012
DOI: 10.3109/0142159x.2012.668245
|View full text |Cite
|
Sign up to set email alerts
|

How we use social media to supplement a novel curriculum in medical education

Abstract: Due to ease of use and widespread applicability, Twitter and Facebook are excellent applications of "push technology" as a means to deliver educational content. This pilot project demonstrates the potential of social media to both supplement and enhance traditional educational methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 7 publications
3
114
0
1
Order By: Relevance
“…Electronic medical records and online textbooks and journals are virtually ubiquitous for this generation [9].electronic learning because it is convenient and efficient and it allows for control over pace, sequence, and content [11]. Chatting/blogging and social media have become important forms of learning in medical education [12,13]. We have anecdotally observed how our Generation Y learners prefer to use textbooks as references and focus on practice questions as the crux of content delivery, a more retrospective form of learning.…”
Section: Generation Ymentioning
confidence: 99%
“…Electronic medical records and online textbooks and journals are virtually ubiquitous for this generation [9].electronic learning because it is convenient and efficient and it allows for control over pace, sequence, and content [11]. Chatting/blogging and social media have become important forms of learning in medical education [12,13]. We have anecdotally observed how our Generation Y learners prefer to use textbooks as references and focus on practice questions as the crux of content delivery, a more retrospective form of learning.…”
Section: Generation Ymentioning
confidence: 99%
“…Our interactive tutorial also provided an opportunity to include formative assessment through multiple choice questions, in addition to testing and questionnaire functionality which allowed us to efficiently evaluate learning and student perceptions. Social media have been successfully utilised for anatomy learning and as a supplement to medical education (Bahner et al, 2012;Hennessy, Kirkpatrick, Smith, & Border, 2016). These resources provide an accessible platform where the educator can faciliate the creation of a community for those students who choose to use artistic learning methods.…”
Section: Tip 12: Incorporate Technologymentioning
confidence: 99%
“…At one institution, physicians in emergency medicine taught students the basics of ultrasonography entirely via Twitter. 10 Although intended for their own students, with Facebook serving as their discussion board, these physicians quickly found that they acquired an international following of others interested in learning ultrasonography. The use of Twitter and Facebook apps on their mobile devices made the course more accessible for everyone.…”
Section: Social Media As An Educational Mediummentioning
confidence: 99%